A Conservative Approach by Unilateral Maximal Single-Muscle Recession Surgery for the Treatment of Cyclic Esotropia. (16th January 2023) - Evereklioglu, Cem; Horozoğlu, Fatih; Sener, Hidayet; Polat, Osman Ahmet
Abstract : Purpose . Cyclic esotropia (alternate-day squint) is a poorly understood form of strabismus that mostly occurs at younger pediatric ages. It demonstrates classically a 48-hour cycle with 24 hours of manifest esotropia and 24 hours of orthotropia, which is conventionally managed by bilateral or unilateral 2-muscle surgery. We aimed to report a child with cyclic esotropia who was surgically treated by a conservative unilateral 1-muscle approach. Methods . Case report. Results . A 3.5-year-old girl presented to the strabismus department with an intermittent esodeviation for 2 years that became cyclic in the last 3 months. The diagnosis of primary classical cyclic esotropia was made after seeing her multiple times on different days. The girl was emmetropic bilaterally, had normal visual acuities in both eyes, and high-angle right esodeviation (45-50 Δ ) with normal laboratory and MRI results. Unilateral maximal single-muscle recession of the right medial rectus was performed, and the child was followed up for 9 months. The girl developed excellent alignment after the surgery both at distance and near without cyclic pattern, and near-normal stereopsis (by animals: 100 sec. of arc) with binocularity was reached. The girl did not experience under- or overcorrection nor have a recurrence postoperatively. Conclusion . This is the first report of "one eye single-muscle" surgery for high-angle cyclic esotropia. Conservative unilateral medial rectus recession seems to be sufficient to permanently block the circadian rhythm and restore binocular fusion and stereopsis.